Evidence for the role of the dopamine D[subscript]3 receptor in mediating methamphetamine addiction - Higley, Amanda E. (Kansas State University, 2009)
Methamphetamine is a potent psychomotor stimulant and a major drug of abuse. There is currently no effective medication available for treatment for methamphetamine addiction. The present study investigated the role of the dopamine D3 receptor on IV methamphetamine self-administration and its effect on methamphetamine induced neurochemical changes. Acute administration of the putative D3 receptor antagonists PG-01037 (10, 30 mg/kg, ip) and SB-277011A (12, 24, mg/kg, ip) significantly decreased the break-point for methamphetamine self-administration under a progressive-ratio (PR) schedule by 45 - 70%. Furthermore, both drugs dose dependently attenuated methamphetamine -triggered reinstatement of drug-seeking behavior in the reinstatement model of relapse. As with other drugs of abuse, the rewarding effects of methamphetamine are believed to be mediated by elevated levels of extracellular dopamine in the mesocorticolimbic system. The present study utilized in vivo microdialysis to examine the neurochemical mechanisms modulating the rewarding effects of methamphetamine actions evident in the various animal models of addiction. In the nucleus accumbens and ventral pallidum, acute methamphetamine (1.0 mg/kg, i.p.,) increased extracellular dopamine by 800 - 900% and decreased GABA by 60 – 65 % in the nucleus accumbens and ventral pallidum. Pretreatment with SB-277011A (12, 24 mg/kg) potentiated the methamphetamine induced dopamine increase but attenuated the methamphetamine-induced GABA decrease. Take together these data suggest that D3 selective antagonists’ pharmacotherapeutic potential in the treatment of methamphetamine addiction may involve a GABAergic mechanism.
Keywords: Methamphetamine; Self-administration; Addiction; Dopamine 3; Microdialysis; Psychology, Psychobiology (0349)